(untitled) (Research, Society and Development, 2025)
One of the greatest challenges of our time is associated with the decarbonization process, because emissions of polluting gases have resulted in countless environmental problems across the planet, affecting, above all, the most vulnerable populations. Thus, the decarbonization process has proven to be essential in guaranteeing a habitable planet, protecting nature, avoiding ecological collapses and ensuring quality of life for present and future generations. With this in mind, the objective of this article is to understand how international communities have worked towards decarbonization, aiming to build more sustainable spaces. To this end, a bibliographic review was carried out, focusing on articles, theses, dissertations, books and materials made available by scientific institutions. The main results showed that the decarbonization process, even with international agreements, has proven to be one of the greatest challenges of our time, since population growth and demand for products have hindered this process. However, international research networks and countries have sought alternatives and policies that value more sustainable and green actions. It is concluded, then, by interpreting the results, that it is necessary to build more sustainable communities that reduce the emission of polluting gases so that we can live on planet Earth with quality conditions and have more sustainable industries and living spaces.